Identification of Recycled Water with an Empirically Derived Symbol Increases Its Probability of Use - Tsagarakis, Konstantinos P; Mellon, Robert C; Stamataki, Elli; Kounalaki, Erofili (Environmental science & technology, 2007)
The experiment described in this paper compared the effects of two systems for labeling recycled water on potential consumers' intention to use this resource; the current identifying symbol used worldwide (purple color for pipes, containers, and tanks) and a new, empirically derived and validated set of symbols that provide specific information on water quality and positive comparative information. In total, 807 face-to-face surveys were carried out. Subjects were asked to rate their intentions for using different qualities of recycled water for commercial agriculture as well as for using products and facilities irrigated with recycled water, either in the presence of the established symbol or the new, empirically derived symbols. Potential consumers' self-reported intentions to use recycled water were reliably higher in the presence of empirically derived symbols with positive comparative information than in the presence of the conventional identification symbol. This program of research provides a model for the application of principles of behavioral psychology to enhance the consumer acceptance of technological advances that preserve natural resources and protect ecosystems.